2021
DOI: 10.3389/fcomm.2021.668862
|View full text |Cite
|
Sign up to set email alerts
|

Staging Expertise in Times of COVID-19: An Analysis of the Science-Policy-Society Interface in the Dutch “Intelligent Lockdown”

Abstract: The corona crisis of 2020 took many by surprise. Quite suddenly, politicians had to make drastic decisions to guarantee public health, affecting basic civil liberties. In justifying their decisions, politicians internationally reverted back to a direct staging of experts to legitimize their proposals for what internationally became known as the “lockdown”. In this article we analyze the performance of the Dutch government that, early on, labeled its approach to COVID-19 as an “intelligent lockdown”. Our analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 39 publications
0
7
0
2
Order By: Relevance
“…On the contrary, emphasizing its ordinary nature highlights its versatility. Our findings suggest the possibility for initiating "dialogic moments" in situations outside of the realms of public engagement sites or organized dialogues, that is, in daily life or "in the wild"; moments that cannot or are hard to be anticipated (see Prettner et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 88%
“…On the contrary, emphasizing its ordinary nature highlights its versatility. Our findings suggest the possibility for initiating "dialogic moments" in situations outside of the realms of public engagement sites or organized dialogues, that is, in daily life or "in the wild"; moments that cannot or are hard to be anticipated (see Prettner et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 88%
“…Most of the advice and decisions were made by the OMT, although there was considerable overlap of personnel between OMT and RIVM (Overheid.nl, 2022). The Director of the RIVM was also the chair of the OMT (Prettner et al, 2021). The OMT included representatives of medical associations such as internal medicine, occupational diseases, microbiologists, infectious diseases, and government agencies such as the Dutch food and consumer product safety authority (RIVM, 2020).…”
Section: Methodology: How Denmark the Netherlands And Sweden Embed Pu...mentioning
confidence: 99%
“…For the most part, politicians and state epidemiologists worked closely together, except that the latter did not believe that schools should close because the RIVM argued that children were unlikely to harbor the virus and that society should protect their social well-being. PM Rutte would eventually yield to public opinion and called for a closure of all schools on March 15, 2020 (Prettner et al, 2021). PM Rutte repeatedly reiterated that the cabinet followed the advice of the OMT, and this advice was based on the fact the Netherlands is "a grown-up country," and "people are glad that they are treated as adults, not as children" (Hoekman et al, 2020).…”
Section: The Netherlands: "Intelligent Lockdown"mentioning
confidence: 99%
“…In this complex scenario, political leaders appealed to their nation by emphasizing their support for science (and scientists) and the need to rely on it (them). Precisely, in Western countries [22], technocratic-oriented messages about the virus and "follow the science" claims characterized governmental and scientific communication during the first phase of the pandemic. As highlighted by [23], appealing to science-and relying on scientific experts-can reinforce policy strategies and increase citizens' policies' acceptance.…”
Section: Science and Politics During The Covid-19 Pandemicmentioning
confidence: 99%
“…In their semiotic analysis of the speeches of Italian, French, and Spanish presidents during the pandemic [27], concluded that the political leaders discursively used the relationship between science and politics to strengthen or justify the strategies chosen. [22] analyzed the Dutch Prime Minister's press conferences and the related Twitter responses in the first stage of the pandemic. Their research showed that in these official statements, scientific experts were presented as entirely reliable and competent to propose COVID-19-related measures, thus deserving to be blindly trusted.…”
Section: Science and Politics During The Covid-19 Pandemicmentioning
confidence: 99%